Peran Taman Bacaan Masyarakat (TBM) untuk Menumbuhkan Minat Baca Masyarakat: - Yusniah Yusniah; Eva Soraya; Ingka Mutiara Rambe; Nurhasanah Harahap; Rifqa Amalia Zuhri; Sarida Sinulingga (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
One of the community library gardens is the smart stock community public library in Deli Serdang, Medan City. This research is to find out how the reading community in the reading garden community, the smart stock community, the city of Deli Serdang in triggering interest in reading. This research applies qualitative research procedures through descriptive and investigative approaches, questions and answers, and documentation as a technique for gathering materials. The findings of this study indicate that TBM Saham Pinang will function as a source of community education and is expected to be of benefit to the community. The increasing number of visitors to TBM shows interest. reading that grew among those who lived around. There are official and repeated visits. It can be concluded that TBM Smart Stock contributes to increasing public interest in reading. and dissemination of information. Keywords: TBM, Reading Gardens, The Role of TBM